Prospects for treated wastewater reuse in agriculture in low- and middle-income countries: systematic analysis and decision-making trees for diverse management approaches - Hosney, H.; Tawfik, Mohamed Hassan; Duker, A.; Steen, P. van der (Elsevier, 2023)
The Middle East and North Africa (MENA) region is suffering from severe water scarcity. Decision-makers in MENA are tackling this challenge by tapping the potential of reusing treated wastewater in agriculture so that large volumes of freshwater sources can be released for priority domestic needs. This aligns with the global efforts to make wastewater reuse mainstream in developing countries by overcoming the technological, infrastructural, health, and socio-cultural barriers that are limiting the expansion of wastewater reuse in agriculture. In this regard, this paper analyses the management modalities of wastewater reuse practices in agriculture in MENA by studying two case studies from Egypt and Jordan. The result of this analysis is a proposed decision-tree tool to help decision-makers in making optimal wastewater reuse decisions based on contextual factors including agricultural field demands, location, freshwater resources, sanitation coverage, and infrastructure, as well as regulations, policies, and restrictions for wastewater reuse. The decision-tree framework was operationalized and validated using the two case studies. The decision tree proved to be an effective framework in assisting decision-makers in making the optimum choice for wastewater reuse in agriculture. It aided the decision maker in evaluating potential reuse options and selecting between several courses of action.